The Effect of Staying Up Late on Food Consumption Patterns and Nutritional Status of Nutrition Students at the Faculty of Psychology and Health, UIN Sunan Ampel Surabaya - Safitri, Septiana; Oktorina, Sarita; Andyarini, Esti Novi (International Conference on Sustainable Health Promotion, 2025)
Staying up late has become a common phenomenon among college students. As many as 40% of adolescents in Indonesia do not sleep 8 hours or more every night. The causes of this habit are diverse, one of which is academic demands in the form of assignments or entertainment games. This habit affects the decline in adolescent health, especially food consumption patterns and nutritional status. This study was conducted to analyze the direct and indirect effects of staying up late on food consumption patterns and nutritional status. This study used a cross-sectional design with a sample of 33 students selected using purposive sampling. Data were collected using questionnaires to assess the habit of staying up late and food consumption patterns, while nutritional status was determined through anthropometric measurements based on Body Mass Index (BMI). Data analysis was performed using path analysis. The results showed that staying up late had no significant effect on dietary patterns (p = 0.705), but had a very significant effect on nutritional status (p = 0.000) with a contribution of 39.1%. Meanwhile, dietary patterns did not significantly affect nutritional status (p = 0.752). Thus, it can be concluded that night owl habits are directly related to the nutritional status of students, while dietary patterns do not act as mediators in this relationship.